A National Digital Diabetes Prevention Programme: Feasible, acceptable and effective?. (13th November 2019) - Murray, E; Valabhji, J; Lavida, A; Henley, W; Daff, K; Irwin, J; Brownlee, L; McGough, B
Abstract: Background: Type 2 Diabetes (T2DM) is a global public health priority affecting 425 million adults with 352 million more at risk of developing T2DM. Intensive group programmes focusing on weight loss and physical activity can prevent or postpone the development of T2DM, but certain groups (e.g working age) find it difficult to attend sessions. Digital options offer a flexible alternative with the potential to widen access and increase uptake. The National Health Service of England (NHSE) has initiated a pilot of a national digital Diabetes Prevention Programme (DPP) to determine its feasibility, acceptability and impact. This is the first national digital DPP in the world, and lessons learnt will be of interest internationally. Methods: Single arm, pre-post design located in 9 geographic areas with a total population of 5.6 million adults. Adults identified in primary care as being at risk of T2DM were referred to a digital diabetes prevention intervention (DDPI). Baseline data included demographic details (age, gender, ethnicity, highest level of education achieved) and clinical data (weight (kg), Body Mass Index (BMI) and glycated haemoglobin (HbA1c mmol/mol)). Clinical data were collected at baseline, 6 and 12 months, with the primary outcome change in HbA1c at 12 months. Results: The programme was effectively implemented in all 9 areas with a total of 5, 053 referrals. 3, 228 (64%) of those referred registered with a DDPI. Mean baseline values for registered patients was BMI 31.1, Weight 87.7 kg and HbA1c 43.4 mmol/mol. To date, 2, 687 patients have reached the 6 month point, of whom 867 dropped out. Mean (95% CI) HbA1c change was -1.6 (-1.8 to -1.4) mmol/mol (n = 1, 264) and mean (95% CI) weight change was -4 (-4.3 to -3.7) kg (n = 1, 184). Conclusions: A national digital DPP is feasible, acceptable to patients and healthcare providers, and appears to be associated with beneficial impacts on HbA1c and weight in those who participate. Key messages: A digital DPP is feasible, acceptable and associated with reductions in weight and HbA1c amongst participants. A digital DPP could be a useful part of a public health strategy to combat T2DM.